Legal Aspects of The Agreement Between Commitment-Making Officials and Providers of Goods and Services At The Ministry of Tourism and Creative Economy - Agus Subhan Muzaki; Basuki Rekso Wibowo (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Government Goods and Services Provider Contract is a type of contract that is routinely carried out by the Government to meet various needs in organizing government activities. Transactions for the procurement of goods and services, namely the Ministry of Tourism and Creative Economy. The research method used is normative research using a statutory, conceptual and field approach. The results of the study are that the work contract between the commitment-making official and the goods and services provider at the Ministry of Tourism and Creative Economy still finds contract clauses that are not fully implemented and not understood by both parties. The impacts that will occur if the contract is not fully implemented and not understood by both parties include triggering contract disputes, even a greater impact is an indication of corruption because the source of funds for the procurement of goods and services is from the APBN. The purpose of this study is to provide education to both parties that the work contract is a guideline that must be understood and obeyed like the law. The ideal concept of direct procurement work contracts in the Ministry of Tourism and Creative Economy includes strengthening the role of APIP in the procurement of goods and services through direct procurement methods through audits, evaluations, reviews, monitoring and other supervision, the creation of standard contracts by including the substance of clauses that generally occur, and the use of sectoral e-catalogs provided by LKPP.